Anti-neutrophil cytoplasmic antibody associated central nervous system vasculitis with brain and spinal cord subarachnoid hemorrhage: A rare case report and review of the literature. (April 2019) - Harland, Tessa A.; Seinfeld, Joshua; Cava, Luis F.; Neumann, Robert T.; Roark, Christopher; Kumpe, David; Case, David
Highlights: Patient was diagnosed with parieto-occipital and spinal subarachnoid hemorrhage. Further work-up revealed ANCA associated central nervous system vasculitis. It is rare to have both a cerebral and spinal subarachnoid hemorrhage. Spinal subarachnoid hemorrhage with vasculitis has not been previously documented. Abstract: This case report describes a 48-year old female who presented with altered mental status, lower extremity weakness, low back pain and a recent history of subjective fevers and night sweats found to have posterior parieto-occipital and spinal subarachnoid hemorrhage on imaging. Further work-up revealed vasculitic changes in the intracranial vasculature and the external carotid artery on angiography. She also demonstrated positivity for perinuclear anti-neutrophil cytoplasmic (p-ANCA) antibodies overall consistent with ANCA associated central nervous system vasculitis (AAV). The present case describes a rare and new presentation of AAV that caused both a cerebral and spinal subarachnoid hemorrhage. There has been no documentation of spinal subarachnoid hemorrhage associated with primary or secondary vasculitis in the literature. Ultimately, this case demonstrates the important finding that AAV can have spinal cord manifestations and cervical vasculature involvement along with the more classic intra-cranial vasculitis findings.